Cameroon : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Financing Assurances Review, and Requests for Waiver of Performance Criterion, Modification of Performance Criteria and Extension of Arrangement; Staff Report; Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cameroon. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses key findings of the Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) for Cameroon. Non-oil economic activity accelerated somewhat in 2007, and inflation declined. However, rising food and fuel prices starting in late 2007, amidst discussions of possible changes to the constitution, led to violent social unrest in February 2008. Program implementation was satisfactory in the second half of 2007. Most quantitative targets, notably on the non-oil primary fiscal deficit, for end-December 2007, were also met.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet